The Efficacy of Physical Education Teachers Amid and Beyond the Pandemic: Basis for an Enrichment Program - Cachero, Vivian F. (RIRAI Publisher, 2025)
This study determined the efficacy of Physical Education teachers and explored how the shift from face-to-face to online learning influenced their teaching practices. The researcher employed a mixed-methods design, utilizing quantitative and qualitative data collection methods.The study showed that the respondents consisted of a diverse age range with a majority of younger teacher’s ages 20-29 years old. This suggests the potential for quicker adoption of new technologies and fitness methodologies in PE curricula. Additionally, the high level of educational attainment majority with Master's degrees indicates a strong foundation in PE theory and best practices. The study revealed that PE teachers possess a strong foundation in various areas but identified some weaknesses. They expressed confidence in content knowledge, instruction, assessment, technology, and extended assistance/accommodation but acknowledged a need for improvement in specific parameters whose scores fell below the overall mean, particularly in teaching racquet games, recreation activities, exercise science concepts application in PE, technology integration in PE, using email and internet for innovative PE, delivering the PE lesson with technology, making rubrics, and authentic assessment for PE and effective approaches to support skill development for PE. The study also emphasized the teachers' resilience and adaptability in creating innovative approaches to deliver PE online. The researcher concluded with the development of the M.E.D.I.E enrichment program. This program aims to enhance the teaching efficacy of teachers in a certain area. This study contributed to a deeper understanding of PE teachers' experiences amid and beyond the pandemic and provided valuable insights for developing programs to enhance their teaching efficacy in a post-pandemic educational landscape.